Valorization of Bilberry (Vaccinium myrtillus L.) Pomace by Enzyme-Assisted Extraction: Process Optimization and Comparison with Conventional Solid-Liquid Extraction - Michail Syrpas; Egle Valanciene; Ernesta Augustiniene; Naglis Malys (MDPI AG, 2021)
Bilberry (Vaccinium myrtillus L.) pomace contains a significant amount of polyphenols and can serve as a basis for food additives, nutraceuticals, and functional foods. Although various techniques can be employed to recover bioactive fractions from berry pomaces, data on enzyme-assisted extraction (EAE) of bilberry pomace are rather scarce. This study aimed to optimize critical EAE parameters using Viscozyme L to obtain a high-yield extract with enhanced antioxidant capacity. Central composite design and response surface methodology evaluating the effect of four independent variables, namely, pH, temperature, extraction time, and enzyme concentration on three responses, were employed to define optimal EAE conditions. Under the optimal conditions (pH: 4.5, temperature 46 °C, 1 h of extraction, and 2 active units (AU) of Viscozyme L/g of pomace), EAE yielded 56.15 g/100 g DW of the water-soluble fraction. Comparison with conventional maceration indicated that EAE, besides the yield, significantly increased the in vitro antioxidant capacity measured by the total phenolic content, ABTS, ORAC, and CUPRAC assays. Moreover, an increase was observed for the measured mono- and disaccharide as well as anthocyanin content. Overall, this study demonstrates the improved efficiency of EAE over conventional solid-liquid extraction to recover fractions with a higher yield and enhanced functional properties in a fast and sustainable manner.